ONTOLOGICAL DRAWINGS: A COLLABORATIVE METHOD FOR RESEARCH WITH AMERINDIAN SOCIETIES - Cacela Brizzi, Yacopo (Espaço Ameríndio, 2021)
The following article explores the ontological dimensions of drawing and its utility as a collaborative research method with Amerindian societies. Focusing on a bibliographic review of Amerindian ethnology and drawing as a method in Anthropology, it attempts to enhance the specificities of drawing as a process and product for different Amazonian contexts while calling attention to the various “uncontrolled equivocations” that need to be taken into consideration. The scrutiny of the composition of drawings through their shapes, colours, materials, and the respective agentive capacities defined by different Amerindian groups place these types of drawing in a special category that may aid researchers in understanding uncharted worlds and expand interest in using drawing as a research method in Anthropology.